2017
DOI: 10.1055/s-0037-1605557
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on Patient-Reported Outcome Measures in Total Knee Arthroplasty

Abstract: Patient expectations and demographics are vital factors in determining patient satisfaction and outcomes from total knee arthroplasty (TKA). This study was a retrospective chart review that analyzed data from TKA patients to determine the impact of age on patient-reported outcomes measures following TKA. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Oxford knee scores were collected as primary outcome measures from 356 consecutive patients who underwent TKA. Oxford knee scores were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…Older age was the only factor that was positively associated with all courses. We analyzed age on a continuous scale, and these findings are in line with a previous study of Townsend et al, who found that TKA patients aged 50-59 years reported worse pain, function, and stiffness scores compared to those aged 60-69 years or older [35]. This might suggest that within the working-age population, specific age classes exist showing different patterns of recovery.…”
Section: Discussionsupporting
confidence: 85%
“…Older age was the only factor that was positively associated with all courses. We analyzed age on a continuous scale, and these findings are in line with a previous study of Townsend et al, who found that TKA patients aged 50-59 years reported worse pain, function, and stiffness scores compared to those aged 60-69 years or older [35]. This might suggest that within the working-age population, specific age classes exist showing different patterns of recovery.…”
Section: Discussionsupporting
confidence: 85%
“…18 This is in line with the previously demonstrated sustained improvements in postoperative OKS between patients in each age group 60 to 69, 70 to 79, and >79. 31 The benefits of arthroplasty were universal, with a comparable improvement in clinical outcomes in all groups. After the initial phase with a higher complication rate, a similar natural history can be expected.…”
Section: Discussionmentioning
confidence: 89%
“…For SF-36 and LEAS, the cohorts 75 years and older had the lowest mean scores at various time points. In the mental component, those < 55 years had the lowest scores postoperatively Older better Townsend [ 29 ] J Knee Surg 2018 356 < 50, 50–59, 60–69, 70–79, > 79 Postoperative WOMAC and overall, pain, and function OKS significantly differed among the age groups ( P < 0.05), with patients younger than 60 years reporting the worst scores in the postoperative time period. Older patients reported better preoperative overall, pain, and function scores and greater post-TKA outcomes than younger patients Merle-Vincent [ 54 ] Joint Bone Spine 2011 264 ≤ 70, > 70, Age older than 70 years at surgery was associated with a higher satisfaction rate (odds ratio of age ≥ 70 years is 3.9 [1.1–14.3]; P = 0.038) Younger better Murphy [ 14 ] Bone Joint J 2018 2838 < 80, ≥ 80 SF-12 PCS, coefficient of ≥ 80-group is − 4.46 (− 6.18, − 2.73), P < 0.001 KJ Oh [ 26 ] Aging Clin Exp Res 2018 79 65–70, ≥ 80 The octogenarian patient group had significantly inferior outcomes for WOMAC and SF-36 score compared to the sexagenarian patient group ( P = 0.009 and P = 0.022, respectively) Naylor [ 28 ] Arthritis Care Res 2018 1289 Post operation 3 years: younger age ( P = 0.0018) was significantly associated with regular physical activity Razak [ 36 ] J Bone Joint Surg Am 2016 3062 Younger age KSS predicted a good outcome at 5 years (OKS: OR of age is 2.66 (2.61–2.71), SF-36 PCS: OR of age is 2.64 (2.59–2.67)) Singh [ 57 ] Osteoarthr Cartil 2010 7139 61–70, 71–80, > 80 Significantly predictors of overall moderate–severe activity limitation 2-years post-TKA was age 71–80 (OR: 2.1 [1.5, 2.8]) and age > 80 (OR: 4.1 [2.7, 6.1]) vs, ...…”
Section: Resultsmentioning
confidence: 99%